Pengabdian Kepada Masyarakat Melalui Kuliah Kerja Nyata (KKN) di Desa Caruban Kecamatan Ringinarum Kabupaten Kendal - Ghufron Nur Hasan; Tata Witanda Ayu; Asna Suraya; Aqil Luthfan (Jurnal Pelayanan Masyarakat, 2024)
Real Work Lecture (KKN) is a form of community service carried out by students as an implementation of the tridharma of higher education. This activity aims to apply the science and technology obtained in college to community life. This article examines the impact and benefits of KKN activities carried out by UIN Walisongo Semarang students in Caruban Village, Ringinarum District. Through a participatory approach, KKN activities in Caruban Village bring positive changes in various aspects of community life, including education, economy, and health. The method used in this research is observation.